Classical and Advanced Theories of Thin Structures Mechanical and Mathematical Aspects - Morassi, Antonio; Paroni, Roberto (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2008)
The book presents an updated state-of-the-art overview of the general aspects and practical applications of the theories of thin structures, through the interaction of several topics, ranging from non-linear thin-films, shells, junctions, beams of different materials and in different contexts (elasticity, plasticity, etc.). Advanced problems like the optimal design and the modeling of thin films made of brittle or phase-transforming materials will be presented as well.